Islamic Views on Money Politic Practices in the Constitutional Election of 2019 - Karto Karto; Akhmad Khisni (Law Development Journal, 2020)
The purpose of this research is to find out and analyze the reasons for the still widespread practice of money politics in the 2019 simultaneous elections. Research methods this uses a normative juridical method, in the form of legal materials written in documents. Which then analyzed qualitatively using the theory of legal certainty and law enforcement. The results of this study are: First, the reasons for the practice of money politics in the 2019 simultaneous elections are known. Second, the view of Islamic law in tackling the practice of money politics/Riswah in the upcoming simultaneous elections. The conclusion in this paper, the causes of money politics include: weak faith, low political education, economic/poverty factors, weak laws, cultural habits and traditions, weak supervision, low education, the last factor is distrust of public figures. View of Islamic Law. Returning to the teachings of Allah is the single most effective way to prevent the practice of money politics, among others, Faith in Allah, people who have faith will be afraid to commit prohibited actions such as bribery, corruption and others, then act, Honest, trustworthy and istiqomah, people. who are able to embody this behavior then the path will be straight, fair, blessed, grateful and qona'ah, if you really return to the concept of Islam, you will not dare to practice money politics.